Open transcatheter valve implantation for mitral annular calcification: One-year outcomesCentral MessagePerspective - Umar Imran Hamid, MD; Anne Gregg, RGN; Peter Ball, FRCR; Colum Owens, MD; Ganesh Manoharan, FRCP; Mark S. Spence, FRCP; Reuben Jeganathan, FRCS (JTCVS Techniques)
Background: Transcatheter mitral valve implantation (TMVI) for native mitral valve pathology with severe mitral annular calcification has emerged as an alternative treatment option to conventional mitral valve surgery. The objective of this study was to evaluate patients who were referred for TMVI with severe mitral annular calcification and their procedural outcomes. Methods: Retrospective analysis of patients from 2017 to 2020 referred for TMVI was carried out. Demographic characteristic details; surgical strategy; perioperative complications; and hospital stay, including 30-day and 1-year mortality, were analyzed. Results: Eleven patients were referred for consideration of TMVI. The 8 patients who underwent TMVI had a median age of 74 years (range, 57-80 years), the median Society of Thoracic Surgeons score was 4.6 (range, 2.4-10.9), and European System for Cardiac Operative Risk Evaluation II score was 5.2% (2%-10.1%). The median cardiopulmonary bypass time and crossclamp times were 170 minutes (range, 150-248 minutes) and 152 minutes (range, 118-214 minutes), respectively. The median hospital stay was 29 days (range, 2-40 days). Thirty-day in hospital mortality was 12%, whereas 1-year mortality was 25%. There was symptomatic improvement with downgrade of New York Heart Association functional class from III or IV to I or II. The 3 patients who were turned down had a median age of 73 years, median Society of Thoracic Surgeons score was 13.4, and median European System for Cardiac Operative Risk Evaluation II score was 5.72%. They were alive at 12 months follow-up from the date of surgical assessment; however, all with New York Heart Association functional class III or IV symptoms. Conclusions: We describe a series demonstrating the technical consideration and capability of transatrial TMVI to treat mitral annular calcification and native mitral valve disease. Our results are favorable when compared with TMVI global registry data for transseptal or transapical approach.